Freeze–Thaw Resistance and Air-Void Analysis of Concrete with Recycled Glass–Pozzolan Using X-ray Micro-Tomography - Krstic, Marija (Materials (Basel), 2020)
Recent studies have shown promising potential for using Glass Pozzolan (GP) as an alternative supplementary cementitious material (SCM) due to the scarcity of fly ash and slag in the United States. However, comprehensive studies on the freeze–thaw (FT) resistance and air void system of mixtures containing GP are lacking. Therefore, this study aimed to evaluate GP’s effect on FT resistance and characterize mixtures with different GP contents, both macro- and microscopically. In this study, six concrete mixes were considered: Three mixes with 20%, 30% and 40% GP as cement replacements and two other comparable mixes with 30% fly ash and 40% slag, as well as a mix with 100% Ordinary Portland cement (OPC) as a reference. Concrete samples were prepared, cured and tested according to the ASTM standards for accelerated FT resistance for 1000 cycles and corresponding dynamic modulus of elasticity (Ed). All the samples showed minimal deterioration and scaling and high F/T resistance with a durability factor of over 90%. The relationships among FT resistance parameters, air-pressured method measurements of fresh concretes and air void analysis parameters of hardened concretes were examined in this study. X-ray micro-tomography (micro-CT scan) was used to evaluate micro-cracks development after 1000 freeze–thaw cycles and to determine spatial parameters of air voids in the concretes. Pore structure properties obtained from mercury intrusion porosimetry (MIP) and N(2) adsorption method showed refined pore structure for higher cement replacement with GP, indicating more gel formation (C-S-H) which was verified by thermogravimetric analysis (TGA).